The Regional Waterway Management System: A Tool for Balancing Coastal Resource Use and Protection - West Coast Inland Navigation District; Florida Sea Grant; Florida Department of Environmental Protection (EDIS)
This document describes the Regional Waterway Managment System (RWMS), a tool for regional planning. The RWMS helps planners and policymakers identify, evaluate, and prioritize channel maintenance and improvement needs. Published February 2005.